2014
DOI: 10.1177/0022034514522060
|View full text |Cite
|
Sign up to set email alerts
|

Dental Caries and Enamelin Haplotype

Abstract: In the literature, the enamelin gene ENAM has been repeatedly designated as a possible candidate for caries susceptibility. Here, we checked whether ENAM variants could increase caries susceptibility. To this aim, we sequenced coding exons and exon-intron boundaries of ENAM in 250 children with a severe caries phenotype and in 149 caries-free patients from 9 French hospital groups. In total, 23 single-nucleotide polymorphisms (SNPs) were found, but none appeared to be responsible for a direct change of ENAM fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…Authors of some studies included in the review observed the SNP phenomenon in genes involved in amelogenesis [Slayton et al, 2005;Deeley et al, 2008;Patir et al, 2008Kang et al, 2011;Olszowski et al, 2012;Shimizu et al, 2012;Tannure et al, 2012a, b;Wang et al, 2012b;Gasse et al, 2013;Chaussain et al, 2014;Duverger et al 2014;Abbasoğlu et al, 2015;Anjomshoaa et al, 2015;Shaffer et al, 2015;Yildiz et al, 2016]. Amelogenesis is a genetically controlled process of enamel development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors of some studies included in the review observed the SNP phenomenon in genes involved in amelogenesis [Slayton et al, 2005;Deeley et al, 2008;Patir et al, 2008Kang et al, 2011;Olszowski et al, 2012;Shimizu et al, 2012;Tannure et al, 2012a, b;Wang et al, 2012b;Gasse et al, 2013;Chaussain et al, 2014;Duverger et al 2014;Abbasoğlu et al, 2015;Anjomshoaa et al, 2015;Shaffer et al, 2015;Yildiz et al, 2016]. Amelogenesis is a genetically controlled process of enamel development.…”
Section: Discussionmentioning
confidence: 99%
“…Although they all coexist in caries aetiology, the research studies usually focus on one of these components. Only a small number of studies was dedicated to analysing the interactions of genetic and environmental factors [Wang et al, 2012b;Chaussain et al, 2014;Abbasoğlu et al, 2015;Shaffer et al, 2015;Yildiz et al, 2016]. Future studies should associate some further information, such as metagenomics, protein-protein interaction, and gene expression, as they may be linked with caries Nibali et al, 2016].…”
Section: Discussionmentioning
confidence: 99%
“…(37,38,39) Specific alleles of ENAM are also associated with high susceptibility to dental caries and the expression level of Enam appears to be determinant for the structure and quality of enamel. (6,40,41) Amelx, which encodes the most abundant EMP, is also important for amelogenesis and mutations of this gene cause AI. (37) The severity and heterogeneity of enamel defects may thus depend on whether Enam is disrupted alone or in association with Amelx.…”
Section: Mmps)mentioning
confidence: 99%
“…Indeed, ENAM mutations have been reported in Amelogenesis Imperfecta (AI) (Lindemeyer et al, 2010; Chan et al, 2011), and have been associated with MIH (Jeremias et al, 2013). Specific alleles of ENAM are also associated with high susceptibility to dental caries (Chaussain et al, 2014) and the expression level of enamelin appears to be determinant for the structure and quality of enamel (Hu et al, 2014). Too much or too little enamelin abolishes the formation of enamel crystals and prism structure.…”
Section: Evidencementioning
confidence: 99%